Transformasi Elektronika Digital dalam Penghitungan dan Rekapitulasi Suara Pemilu/Pilkada: Analisis Eksistensi Sistem di Persidangan Perselisihan Hasil di Mahkamah Konstitusi - Mpesau, Alasman (LP3M, Universitas Muhammadiyah Kendari, 2024)
This study examines the use of digital electronic systems in General-Regional Elections as evidence in the Constitutional Court's dispute over Vote Counting Results. Focusing on the Rekapitulasi Information System (SIREKAP), the research explores the existence and evidential strength of SIREKAP as a mandatory administrative action during the electoral process. In the context of normative law, this research utilizes primary and secondary data related to electoral laws and relevant legal materials. Through observation and documentation methods, the data is analyzed by organizing, sorting, and categorizing information. The study demonstrates that SIREKAP has a legal basis in the Regulation of the General Election Commission, making it a legally accountable piece of evidence. This normative legal research contributes significantly to understanding the role of digital electronic systems in General-Regional Elections in the context of evidentiary support during PHPU in the MK. The results are expected to provide insights into the role of SIREKAP as an instrument supporting transparency and accountability in democracy, particularly in addressing the complexity and challenges of managing General Elections/Regional Elections.